(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This research aims to examine the methodology of Imam Abu Mansur al-Maturidi al-Samarqandi (d. 333 AH) in interpreting the verses of the horizons and souls (macrocosmic and microcosmic verses) in his book Ta’wilat al-Qur’an, elucidating how he transformed these verses into systematic theological proofs that contribute to building a comprehensive epistemological vision for Ahl al-Sunnah wa al-Jama’ah. The research stems from the postulate that the verses concerning the universe and humanity occupy a central position in the Islamic epistemological structure, serving as a bridge between the physical world and the metaphysical realm, and between sensory experience and faith-based reasoning. It focuses on analyzing selected models from the Surahs of Al-A’raf, Al-Furqan, An-Naml, Al-Qasas, As-Sajdah, and Al-Mu’minun. The study highlights al-Maturidi’s objectives in employing these verses to establish the tenets of Tawhid (monotheism), divine power, wisdom, teleological purpose, the affirmation of resurrection, and the critique of opposing sects such as the Mu’tazilites, Dualists, and Materialists.